Urban Forestry and Compact Cities - Mohd. Yaman, Maheran; Nik Abdul Rahman, Nik Ismail Azlan (IIUM, 2009)
ABSTRACT This article expresses concern that many Third World urban and landscape planners do not adequately made good their understanding of tropical environmental habitats. They may appreciate the City’s Beautiful Movement ideas like planning of new towns and Garden Cities, but ideas of these are not tropical climate oriented ideals. What is suggested is that we should build our own ideas from what Nature has given us- dense tropical forest canopies to envelope our cities that will make outdoor activities pleasanter as well as right-sizing the urban spread to render them pedestrian-friendly. The ensuing approach then is to configure urban landscaping specifically adapted for tropical regions that will provide a living heritage for mankind. Keywords: tropical urban habitats, urban forestry and right-sizing the city